"A room of one's own": A phenomenological investigation of class, age, gender and politics of institutional change regarding adult students on campus. - Peggy A. Sissel; Margaret Birdsong; Barbara Silaski (Adult Education Research Conference, 1997)
This collaborative phenomenological investigation reveals the experience of adult student advocates in a university setting. The setting was interpreted as being mediated by interlocking systems of oppression. Issues included concepts of class, age, gender, and institutional politics related to resource allocation and meaning about the nature and needs of adult students.